Experimental study of improvised tesla micro-turbine - Muhammad Nazri, Muhammad Nor Ikmal; Mohamad Fadhir, Nurul Qistina; Bajuri, Farid; Basri, Ernnie Ilyani; Basri, Adi Azriff (Aeronautical and Astronautical Society of the Republic of China, Taiwan, 2024)
The Tesla turbine has revolutionized conventional turbine technology by employing friction and viscous forces on stacked discs instead of blades. The Tesla turbine is still distinguished by its remarkable efficiency in capturing the fluid energy through the boundary layer adhesion and cohesion principle. While Tesla turbines can achieve impressive rotational speeds, they also have a limitation in torque, which becomes a substantial obstacle in its application. Hence, the main objective of this study is to improvise the design of the Tesla turbine and analyze the new design’s rotational speed and voltage generation with different inlet pressures. To accomplish this, the new design of the Tesla turbine discs is developed and fabricated. The study is then proceeded with the experimental work by conducting the RPM and voltage generation tests, which are performed to gather quantitative data to assess the best disk spacing and test the performance and feasibility of the improvised Tesla turbine. In general, the initial result has shown that the smallest disc spacing of 0.2 cm produces the highest RPM compared to the other models. The effect of design where blades are attached to the upper part of the pure Tesla discs (model 4) is found to perform the best in terms of RPM, which is higher by three times of the original Tesla turbine at 20 psi. At the highest inlet pressure, which is 80 psi, model 4 shows the highest rotational speed and voltage production at 3881 rpm and 19 V, respectively, when compared to the other models. It can be concluded that the improvisation of the Tesla turbine has performed better than the original. By achieving high RPM and voltage, the power output is enhanced for energy harvesting applications.